The hematologic complications of chemotherapy in lung cancer patients - Słowik-Gabryelska, Anna; Opozda, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2000)
The unsatisfactory effects and toxity of anticancer chemotherapy in lung cancer patients lead to the opinion that chemical cytotoxic treatment may worsen the quality of life more than the neoplasm itself. That was the rationale of the examinations of hematologic side effects of chemotherapy in lung cancer patients. The aim of these examinations was: establish the intensity of hematologic side effects of chemotherapy in lung cancer patients. Material and method: in 309 lung cancer patients the intensity of hematologic side effects of chemotherapy was assessed. The intensity of lesions was estimated in 5 degree WHO scale. The intensity of side effects was analysed in relation with the age, gender, drug combination, number of therapeutic cycles, results of treatment, cellular type and stage of cancer. The results: in 93% of patients hematologic disorders after chemotherapy were seen. In more than 90% of patients there was neutropenia, which included in 30% agranulocytosis with infections. In these patients, the intensive bone marrow stimulation and antibiotic treatment was necessary. In about 80% of patients anaemia was seen. In 17% of patients anaemia was severe, and anticancer treatment had to be terminated. In 50% of patients, the number of platelets was decreased, and in 9% of patients the bleedings occured. The dependence of hematologic side effects of chemotherapy upon the gender and cellular type of cancer was not established. But there was very close dependence on the age, the drug combinations, number of cytostatic cycles and stage of cancer.